Managerial bonuses and subordinate mistreatment - Nikiforakis, Nikos; Oechssler, Joerg; Shah, Anwar (European economic review, 2019)
Can performance bonuses increase the likelihood that managers coerce their subordinates into exerting high levels of effort when doing so promotes neither efficiency nor equity? We consider a laboratory setting in which managers compete to obtain a large bonus at the end of the experiment and the probability of obtaining it depends partly on the effort exerted by the subordinates. We find that managers are more than twice as likely to punish subordinates exerting “fair” levels of effort if they compete for individual bonuses than when there are no bonuses. This is not the case when they compete for pooled bonuses - giving managers discretionary power over how to share them with their subordinates - as most subordinates willingly exert maximal effort. A model in which individuals are assumed to care about equity captures subordinates’ behavior well. Managers’ willingness to coerce subordinates into exerting unfairly high levels of effort, on the other hand, cannot be readily accounted for by any of the existing models of social preferences.
Gesehen am 10.09.2019